Revolutionizing Education: Unleashing the Power of the ADDIE Model for Effective Teaching and Learning - Moses Adeleke Adeoye; Kadek Adrian Surya Indra Wirawan; Made Shania Satya Pradnyani; Nyoman Intan Septiarini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
In recent years, the ADDIE Model has emerged as a robust framework that revolutionizes education by providing a systematic approach to instructional design and development. This research explores various aspects of the ADDIE model and its potential to transform education in the 21st century for effective teaching and learning. This type of qualitative research involves a comprehensive literature review using a data collection method through surveys. The data analysis technique uses qualitative descriptive analysis. The research results, namely through a comprehensive analysis of each phase of the model, this paper highlights the benefits of applying the ADDIE model as a pedagogical approach and offers insights into its application. The main goal is to illustrate how the ADDIE Model can revolutionize education and pave the way to a more engaging and impactful learning environment. The ADDIE model has the potential to revolutionize education by providing educators with a systematic approach to instructional design. By incorporating key components and principles into teaching practices, educators can create engaging and effective learning experiences for students.